DEVELOPING SUPPLEMENTARY READING MATERIALS FOR THE STUDENTS OF EIGHTH GRADERS NURUS SALAFIYAH PROBOLINGGO - zainuddin zainuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Developing Supplementary Reading Materials for the students of eighth Graders at Nurus Salafiyah Probolinggo. It modified Latief model (2009); the researcher developed material based on data analysis taken from a preliminary study. The material was validated and tried-out to class VIII-B of Nurus Salafiyah Probolinggo. The result showed that this study and the product have successfully answered the students' needs in reading skills. Therefore, the product could be used for the eighth-grader students of Nurus Salafiyah Probolinggo